1997
DOI: 10.1136/ard.56.12.744
|View full text |Cite
|
Sign up to set email alerts
|

Fcgamma RIIa polymorphism in systemic lupus erythematosus

Abstract: Objectives-Polymorphism of the phagocyte IgG receptor Fc RIIa may modulate immune complex mediated inflammation, particularly when immune complexes contain IgG2. Previous studies suggest that this polymorphism may be an important risk factor for lupus nephritis. Fc RIIa is biallelic, the alleles R and H each having a gene frequency of about 50%. Nephritis has been associated with an increased frequency of the R allele. The frequency of common Fc RIIa alleles was examined in white subjects from the United Kingd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 13 publications
3
44
0
1
Order By: Relevance
“…Other studies, however, did not find an association within their respective European populations. [78][79][80] These differences may be attributable to genetic variances among different ethnic groups. Fc␥RIIA does appear to play an important role in some SLE populations, while playing a smaller (maybe even undetectable) role in others.…”
Section: Fc␥ Receptorsmentioning
confidence: 99%
“…Other studies, however, did not find an association within their respective European populations. [78][79][80] These differences may be attributable to genetic variances among different ethnic groups. Fc␥RIIA does appear to play an important role in some SLE populations, while playing a smaller (maybe even undetectable) role in others.…”
Section: Fc␥ Receptorsmentioning
confidence: 99%
“…13 Based on the presence of functionally relevant polymorphisms, Fc␥Rs have been considered as attractive candidates for the susceptibility genes to systemic lupus 15,16 while no association was found in AfroCaribbean, Chinese, British and Greek Caucasians. 17,18 The latter studies may lack the statistical power and the results could represent false negatives. A recent study reported that Fc␥RIIA-131H/R polymorphism was associated with clinical symptoms, rather than the development, of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…There have been at least four such studies [7,8,10,11] although in one of them [10], FcγRIIa-R131/R131 allotype was significantly associated with some clinical and serological parameters of the disease despite the absence of any influence on the risk for SLE in general. The role of FcγRIIa polymorphism in SLE is clearly uncertain, particularly on the basis of data reported for Caucasian and black patients.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to demonstrate any association between FcγRIIa allotypes and SLE with or without nephritis has now been reported in several Caucasian [7,8,10], AfroCaribbean [7], Chinese [7,11], and Malay [11] ethnic groups (table 3). Botto et al [7] studied 215 Caucasoid, 70 Afro-Caribbean, and 46 Chinese patients with SLE and 259, 77, and 49 ethnically matched controls, respectively.…”
Section: Studies Demonstrating No Association Between Fcγriia Polymormentioning
confidence: 99%
See 1 more Smart Citation